PENGARUH MEDIA 3DS MAX MAKER TERHADAP HASIL BELAJAR SISWA - Lalu Herman Susandi; Zinnurain Zinnurain (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2019)
Learning outcomesare the main thing in the world of education. However, in the learning process at Riyadlul Anwar Islamic Senior High School learning outcomes of each student are different. One of the influencing factors is teacher still uses conventional and monotonous learning media, it is causes less active participation in the learning process. On that basis, researches took another alternative by applying Max Maker 3Ds Media on student learning. The purpose of this research was to analyze the influence of 3Ds Max Maker media on student learning outcomes in ICT Subjects Class XI in Riyadlul Anwar Islamic Senior High Middle Lombok 2018/2019 Academic Year. The technique used in determining population is population study technique because the population is 21 students. The method of data collection uses the test method as the principical method and documentation as complementary method. Data analysis using the t-test formula. After research was conducted, research data was entered into the work table, then entered into formula. The results of the t-test show the value of t-count is greater than t-table at significant level of 5% with db=21,1 =20 (3,436>2,086). Based on the research findings. So, it can be concluded that there is an Effect of 3Ds Max Maker Media on Student Learning Outcomes in ICT Subjects at Riyadlul Anwar Islamic Senior High School Middle Lombok 2018/2019 Academic Year. It can be concluded that the results of this research are “significant”